Selinunt, Italien. Selinunt. Die Arbeiten des Jahres 2019 - Dally, Ortwin; Albers, Jon; Bücherl, Heike; Helas, Sophie; Henning, Agnes; Mège, Frédéric; Coutelas, Arnaud; Lindroos, Alf; Olsen, Jesper (e-Forschungsberichte des DAI, 2020)
The report contains the results of various research and excavation activities of the DAI Rome and its cooperation partners in Selinunt from the year 2019. The third and final campaign took place in the Agora, work continued on temples A and O, floor examinations were carried out in various houses on the Acropolis, a new DFG project was started in the east port, and in the Baglio Florio of the Parco Archeologico di Selinunte at the end of the year an exhibition on the long-term research of the DAI Rome was inaugurated on the Agora.